2021
DOI: 10.1111/exsy.12787
|View full text |Cite
|
Sign up to set email alerts
|

Efficient detection of Parkinson's disease using deep learning techniques over medical data

Abstract: Parkinson's disease is a degenerative disease that leads to brain disorder and nonfunctioning of different body parts. Deep learning tools like artificial neural network (ANN), convolution neural network (CNN), regression Analysis (RA), and so on, has been considered to a great extent in recent days. Several data sets based on the motor and nonmotor symptoms are applied to different classifier for correct identification of Parkinson's patient from healthy people. In this paper, hybridization of two deep learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…The calculated outcome shows that the suggested algorithm is superior with 93.46% accuracy. [11] Vyas, T et al, "Parkinson's illness diagnosis using deep learning". We have used MRI (magnetic resonance imaging) brain images for this reason.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The calculated outcome shows that the suggested algorithm is superior with 93.46% accuracy. [11] Vyas, T et al, "Parkinson's illness diagnosis using deep learning". We have used MRI (magnetic resonance imaging) brain images for this reason.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although DL is proved to be very effective, the use of low-interpretability models may however evoke the resistance of clinicians asking for high-level evidence in clinical practice, in turn resulting in the overfitting phenomenon as well as a lack of generalization. ML and DL models for the assessment of PD were compared mainly for binary classification tasks (healthy vs. PD), involving acoustic features as an input to ML pipelines: apart from a few exceptions [ 38 , 39 ], the majority of studies reported better performance from of DL models [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. Similar results are also reported in works employing deep features extracted from spectrograms [ 46 , 47 , 48 , 49 , 50 , 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…When brain networks are incorrectly connected to coordinate activities, certain disorders in the human body arise [1,2]. Some of the most common neurodevelopmental disorders are autism spectrum disorder (ASD) [3], schizophrenia [4], attention defcit hyperactivity disorder (ADHD) [5], epilepsy [6], Parkinson's disease [7], obsessive-compulsive disorder [8], and bipolar disorder (BD) [9].…”
Section: Introductionmentioning
confidence: 99%